2010
DOI: 10.1177/0269215509353267
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two accelerated clinical pathways - after total knee replacement how fast can we really go?

Abstract: Early postoperative functional process indicators tended to be higher within the optimized pathway group, but the main effects flattened over the course of the first eight postoperative days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
1
25
0
4
Order By: Relevance
“…The early ambulation in the study group appeared to correlate with decreased LOS as well. This is consistent with other studies [15,16]. The liposomal bupivacaine group stayed 0.29 fewer days in the hospital.…”
Section: Discussionsupporting
confidence: 93%
“…The early ambulation in the study group appeared to correlate with decreased LOS as well. This is consistent with other studies [15,16]. The liposomal bupivacaine group stayed 0.29 fewer days in the hospital.…”
Section: Discussionsupporting
confidence: 93%
“…Renkawitz showed a flattening of benefits at day 8 post operation in a pathway of further optimisation of an existing accelerated clinical pathway protocol after total knee replacement (which included ultra-early/ doubled physiotherapy and use of motor-driven continuous passive motion machine units). 6 Lenssen showed that two daily sessions received by an experimental group and one by a comparison group following total knee arthroplasty resulted in no between-group difference in the primary outcome measure of range of motion. 29 Perhaps early mobilization within the first 24 post operative hours and one therapy session per day, as was typical in the trials included in this systematic review, could be considered as a benchmark.…”
Section: Study or Subgroupmentioning
confidence: 99%
“…Undesired events caused by early mobilization, such as hemodynamic instability or the increased risk of falling, did not occur significantly more frequently when compared to control groups without early mobilization (Guerra et al 2015). Other studies were able to demonstrate lower risks of DTV, PE, chest infections and urinary retention during early mobilization (Renkawitz et al 2010). …”
Section: J Physiotherapeutic Measures and Mobilitymentioning
confidence: 91%